RBC-hitchhiking PLGA nanoparticles loading β-glucan as a delivery system to enhance in vitro and in vivo immune responses in mice - Li, Sheng; Wang, Yao; Liu, Qianqian; Tang, Feng; Zhang, Xinnan; Yang, Shuyao; Wang, Qiran; Yang, Qian; Li, Shanshan; Liu, Jie; Han, Lu; Liao, Yi; et al. (Frontiers in Veterinary Science, 2024)
Red blood cells (RBCs) naturally trap some bacterial pathogens in the circulation and kill them by oxidative stress. Following neutralization, the bacteria are presented to antigen-presenting cells in the spleen by the RBCs. This ability of RBCs has been harnessed to develop a system where they play a crucial role in enhancing the immune response, offering a novel approach to enhance the body’s immunity. In this work, a conjugate, G-OVA, was formed by connecting β-glucan and OVA through a disulfide bond. Poly (lactic-co-glycolic acid) (PLGA) was then employed to encapsulate G-OVA, yielding G-OVA-PLGA. Finally, the nanoparticles were adsorbed onto RBCs to develop G-OVA-PLGA@RBC. The results demonstrated that the delivery of nanoparticles by RBCs enhanced the antibody response to antigens both in vitro and in vivo. The objective of this study was to investigate the increased immune activity of G-OVA-PLGA nanoparticles facilitated by RBCs transportation and to elucidate some of its underlying mechanisms. These findings are anticipated to contribute valuable insights for the development of efficient and safe immune enhancers.